Efektivitas Pelayanan Angkutan Bus Sekolah yang Dikelola oleh Badan Usaha Milik Sekolah - Za, Zulfiandry (Advances In Social Humanities Research, 2024)
School transportation can be one alternative that can be applied to change inefficient student travel behavior, namely the use of vehicles with low occupancy and safety levels such as four-wheeled private vehicles and motorcycles, while improving public transportation services for students who do not have private vehicles. This Best Practice aims to describe school transportation management consisting of; program preparation, management structure, implementation, evaluation, problems and solutions. This research uses a qualitative approach with the type of case study research. Research data collection techniques are interviews, observations and documentation. The results showed that school transportation services were prepared by the School-Owned Enterprises (BUMS) SMPN 3 Pangkalan Kerinci referring to the principles of school transportation services. The implementation and evaluation are managed by the foundation and involve the school. Some problems are faced, but there are solutions implemented to overcome them.